The Second Epistle to the Corinthians. By Murray J. Harris - Gooder, Paula (The journal of theological studies, 2007)
The aim of the New International Greek Testament commentary series is, in the words of the series editors, to ‘cater particularly to the needs of students of the Greek text’ (p. xii). This volume seeks, possibly even more than some of the others in this series, to live up to this aim. Harris states in the preface to his work that ‘Scripture cannot be understood theologically unless it has first been understood grammatically’ (p. xiv).